Personalized Remote Monitoring of the Atrial Fibrillation Patients with Electronic Implant Devices. Issue 2 (29th June 2011) - Laleci, Gokce B.; Dogac, Asuman; Yuksel, Mustafa; Kabak, Yildiray; Arbelo, Elena; Danmayr, Franz; Hinterbuchner, Lynne; Chronaki, Catherine; Eichelberg, Marco; Lüpkes, Christian
Abstract : Cardiovascular Implantable Electronic Devices (CIED) are gaining popularity in treating patients with heart disease. Remote monitoring through care management systems enables continuous surveillance of such patients by checking device functions and clinical events. These care management systems include decision support capabilities based on clinical guidelines. Data input to such systems are from different information sources including medical devices and Electronic Health Records (EHRs). Although evidence-based clinical guidelines provides numerous benefits such as standardized care, reduced costs, efficient and effective care management, they are currently underutilized in clinical practice due to interoperability problems among different healthcare data sources. In this paper, we introduce the iCARDEA care management system for atrial fibrillation patients with implant devices and describe how the iCARDEA care plan engine executes the clinical guidelines by seamlessly accessing the EHR systems and the CIED data through standard interfaces.